E-ARCHIVE INFORMATION SYSTEM FOR COOPERATION DOCUMENTS AT THE COMMUNICATION AND INFORMATICS OFFICE OF EAST LAMPUNG REGENCY - Fuad Arif Baharudin; Dona Yuliawati (PT. GWEX NET PUBLISHER, 2026)
The development of information technology encourages government agencies to carry out digital transformation in archive management to increase administrative efficiency and effectiveness. The Communication and Information Service of East Lampung Regency still faces obstacles in the management of cooperation documents that are carried out manually, such as difficulties in searching archives and the risk of data loss. This research aims to design and build a web-based Cooperation Document E-Archive Information System as a solution to these problems. The system development method used is the Prototype method, which allows direct interaction between developers and users in the system development process. The system is built using PHP 8.1 with the Model-View-Controller (MVC) architecture and MySQL 8.0 as the database. Black-box testing conducted on 25 test cases achieved a 100% success rate, confirming that all functional requirements were met without errors. User Acceptance Testing (UAT) yielded an acceptance score of 92%, indicating a high level of user satisfaction and system usability. These results demonstrate that the developed system effectively simplifies the document management process—from storage and retrieval to structured archival grouping, thereby improving work efficiency and supporting the implementation of the Electronic-Based Government System (SPBE) in the relevant agencies.